2015
DOI: 10.3109/13651501.2015.1043133
|View full text |Cite
|
Sign up to set email alerts
|

Association of TMEM132D, COMT, and GABRA6 genotypes with cingulate, frontal cortex and hippocampal emotional processing in panic and major depressive disorder

Abstract: These results suggest that TMEM132D, GABRA6, and COMT variants may increase vulnerability to panic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 91 publications
2
17
1
Order By: Relevance
“…Previous research points to the possible involvement of GABA in the propensity of anxious and fearful traits and temperaments via its GABA-A receptor-mediated inhibitory effects with even minor genetic variation possibly contributing to an alteration in anxiety-related traits and individual differences in threat-related responses 26 , 27 . Specifically, GABRA6 TT carriers were shown to exhibit increased harm avoidance and anticipatory worry 26 , 28 , and T carrier panic disorder patients showed increased reaction to fearful faces in an fMRI study 24 thus suggesting an association between GABRA6 and different aspects of anxiety 14 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research points to the possible involvement of GABA in the propensity of anxious and fearful traits and temperaments via its GABA-A receptor-mediated inhibitory effects with even minor genetic variation possibly contributing to an alteration in anxiety-related traits and individual differences in threat-related responses 26 , 27 . Specifically, GABRA6 TT carriers were shown to exhibit increased harm avoidance and anticipatory worry 26 , 28 , and T carrier panic disorder patients showed increased reaction to fearful faces in an fMRI study 24 thus suggesting an association between GABRA6 and different aspects of anxiety 14 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous results suggested an association between hormonal and psychological stress response and the GABRA6 gene. Variations in GABRA6 and specifically rs3219151 T allele was found to be related to higher baseline salivary cortisol levels 13 and higher ACTH, cortisol and blood pressure increase upon stress exposure in several studies 14 , 24 , 25 . These results suggest that decreased inhibition of the HPA axis due to GABA deficits may contribute to increased hormonal and physiological stress response 14 which is well-known to be associated with risks of developing mental health problems including depression and suicide.…”
Section: Discussionmentioning
confidence: 95%
“…Fig 7D). Notably, Gabra6, among the most highly dysregulated genes in Pclo KO rats, was also not detectable in the hypothalamus and cortex samples of the MDD rat model (Fig 7E), connecting Gabra6 with both Pclo and MDD phenotypes [20,45].…”
Section: Recessive Pclo Traits Are Mappable To Allelic Markers For Mamentioning
confidence: 96%
“…By analogy, the pre-copulatory mating behavior and aggression phenotypes reported here in Pclo SBΔ4-25 rats demonstrate Piccolo's potential control over sensory responses to social cues. Importantly, while both Piccolo and Gabra6 variants are associated with MDD and altered emotional processing based on studies in humans [20,45], no direct sexual connection to either gene has been reported in humans. The functional significance of the tight control of Gabra6 expression by Pclo has yet to be investigated, but one possibility is that a loss of synaptic integrity leads to Gabra6 down-regulation [58].…”
Section: Affective Disorder and Limbic System Neurotransmission Phenomentioning
confidence: 99%
“…Symptom severity scores in the COMT AA/AG genotype group were positively correlated with the FA in WM tracts. Inoue et al[118] investigated possible associations of COMT, human TransMEMbrane protein 132D (TMEM132D), and GABA receptor alpha 6 subunit (GABRA6) genotypes in PD patients and healthy controls. The polymorphisms rs4680 in COMT and rs3219151 in GABRA6 showed positive associations with PD.…”
Section: Resultsmentioning
confidence: 99%